Lactobacillus Eats Amyloid Plaque and Post-Biotically Attenuates Senescence Due to Repeat Expansion Disorder and Alzheimer's Disease - Suresh C. Tyagi (MDPI AG, 2024)
Patients with Alzheimer's disease and related dementia (ADRD) are faced with a formidable challenge of focal amyloid deposits and cerebral amyloid angiopathy (CAA). The treatment of amyloid deposits in ADRD by targeting only oxidative stress, inflammation and hyperlipidemia has not yielded significant positive clinical outcomes. The chronic high-fat diet (HFD), or gut dysbiosis, is one of the major contributors of ADRD in part by disrupted transport, epigenetic DNMT1 and the folate 1-carbon metabolism (FOCM) cycle, i.e., rhythmic methylation/de-methylation on DNA, an active part of epigenetic memory during genes turning off and on by the gene writer (DNMT1) and eraser (TET2/FTO) and the transsulfuration pathway by mitochondrial 3-mercaptopyruvate sulfur transferase (3MST)-producing H2S. The repeat CAG expansion and m6A disorder causes senescence and AD. We aim to target the paradigm-shift pathway of the gut-brain microbiome axis that selectively inhibits amyloid deposits and increases mitochondrial transsulfuration and H2S. We have observed an increase in DNMT1 and decreased FTO levels in the cortex of the brain of AD mice. Interestingly, we also observed that probiotic lactobacillus-producing post-biotic folate and lactone/ketone effectively prevented FOCM-associated gut dysbiosis and amyloid deposits. The s-adenosine-methionine (SAM) transporter (SLC25A) was increased by hyperhomocysteinemia (HHcy). Thus, we hypothesize that chronic gut dysbiosis induces SLC25A, the gene writer, and HHcy, and decreases the gene eraser, leading to a decrease in SLC7A and mitochondrial transsulfuration H2S production and bioenergetics. Lactobacillus engulfs lipids/cholesterol and a tri-directional post-biotic, folic acid (an antioxidant and inhibitor of beta amyloid deposits; reduces Hcy levels), and the lactate ketone body (fuel for mitochondria) producer increases SLC7A and H2S (an antioxidant, potent vasodilator and neurotransmitter gas) production and inhibits amyloid deposits. Therefore, it is important to discuss whether lactobacillus downregulates SLC25A and DNMT1 and upregulates TET2/FTO, inhibiting β-amyloid deposits by lowering homocysteine. It is also important to discuss whether lactobacillus upregulates SLC7A and inhibits β-amyloid deposits by increasing the mitochondrial transsulfuration of H2S production.